Investigation of Vortical Structures and Turbulence Characteristics in Corner Separation in an Axial Compressor Stator Using DDES - Jun Li; Jun Hu; Chenkai Zhang (Energies, 2020)
In order to investigate the flow structure and unsteady behavior of three-dimensional corner separation, a delayed detached-eddy simulation (DDES) method based on the Spalart–Allmaras (SA) model is performed on the third-stage stator of a multistage low-speed axial compressor. The stator simulation is validated by experiments before flow mechanism analysis. The complicated flow fields in the stator are then described step by step. Firstly, the structure and development process of vortices in corner separation flow are analyzed. Secondly, the velocity histogram of the monitor points in the mainstream and corner separation regions is obtained, and the velocity distribution of the corner separation region is discussed. Finally, Reynolds stress, Lumley anisotropy, turbulence energy spectra, and helicity density are discussed to understand the turbulence behavior of the corner separation flow in the stator. The results show that the corner separation appears at even the design condition and different kinds of vortical structures appear in the stator hub corner. The unsteadiness of corner separation flow is mainly reflected in the separation on the suction side of the blade and the wake shedding. Turbulence anisotropy and energy backscatter are found to be dominant in the separation region, which is correlated to the high shear stress.